Exosomal NAMPT from chronic lymphocytic leukemia cells orchestrate monocyte survival and phenotype under endoplasmic reticulum stress. Issue 1 (9th November 2022) - Ni, Jing; Zhang, Ju; Liu, Jiatao; Fan, Lulu; Lin, Xiao; Yu, Hanqing; Sun, Guoping
Abstract: Endoplasmic reticulum (ER) stress has been reported to be transmitted from tumor cells to immune cells via exosome and implicated in immune escape. However, the influence of ER stress on monocytes in chronic lymphocytic leukemia (CLL) cells is largely unknown. Here, we observed the expression of ER stress markers (GRP78, ATF6, PERK, IRE1a, and XBP1s) in CLL cells. The increasing mRNA expression of these ER stress response components was positively correlated with more aggressive disease. Exosome from ER stress inducer tunicamycin (TM)‐primed CLL cells (ERS‐exo) up‐regulated the expression of ER stress marker on monocytes, indicating ER stress is transmissible in vitro via exosome. Treatment with ERS‐exo promoted the survival of monocytes and induced phenotypic changes with a significantly larger percentage of CD14 + CD16 + monocytes. Finally, we identified exosome‐mediated transfer of extracellular nicotinamide phosphoribosyltransferase (eNAMPT) from ER stressed CLL cells into monocytes as a novel mechanism through which ERS‐exo regulated monocytes. Exosomal eNAMPT up‐regulated nicotinamide adenine dinucleotide (NAD + ) production which subsequently activated SIRT1‐C/EBPβ signaling pathway in monocytes. Our results suggest the role of ER stress in mediating immunological dysfunction in CLL.